2021
DOI: 10.1371/journal.pone.0244415
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine confidence and hesitancy among health care workers: A cross-sectional survey from a MERS-CoV experienced nation

Abstract: Objectives This study aimed to identify coronavirus disease 2019 (COVID-19) vaccine perception, acceptance, confidence, hesitancy, and barriers among health care workers (HCWs). Methods An online national cross-sectional pilot-validated questionnaire was self-administered by HCWs in Saudi Arabia, which is a nation with MERS-CoV experience. The main outcome variable was HCWs’ acceptance of COVID-19 vaccine candidates. The factors associated with vaccination acceptance were identified through a logistic regres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
48
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 49 publications
5
48
1
3
Order By: Relevance
“…Of concern, the perceived effectiveness of the current COVID-19 vaccines against Omicron variant among the surveyed HCWs was 67%, while one third expressed possible lack of efficacy. This represent a decline in HCWs perception of vaccine efficacy compared to our earlier study done on December 2020 during the initial rollout of COVID-19 vaccine which was 80.2%[19]. Such finding reflects declining confidence in vaccine efficacy against emerging variants which is noteworthy since concerns about efficacy have been stated as one of the main reasons for vaccine hesitancy[25].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Of concern, the perceived effectiveness of the current COVID-19 vaccines against Omicron variant among the surveyed HCWs was 67%, while one third expressed possible lack of efficacy. This represent a decline in HCWs perception of vaccine efficacy compared to our earlier study done on December 2020 during the initial rollout of COVID-19 vaccine which was 80.2%[19]. Such finding reflects declining confidence in vaccine efficacy against emerging variants which is noteworthy since concerns about efficacy have been stated as one of the main reasons for vaccine hesitancy[25].…”
Section: Discussionmentioning
confidence: 82%
“…Increased access to peer-reviewed journals should be strongly encouraged among HCWs. Exploring different hindering factors and the true role of open access journals in distributing science within healthcare communities, especially during times of global health crisis, is urgently needed [19]. In an attempt to combat vaccine hesitancy and to confront the new surge in cases, KSA MoH mandated COVID-19 vaccination and made it a requirement to enter public or private institutions, including's shops, mall and governmental offices.…”
Section: Discussionmentioning
confidence: 99%
“…The current study’s findings concerning vaccine acceptance are in line with those of prior studies conducted in other parts of the world. A cross-sectional conducted in the Kingdom of Saudi Arabia (KSA) prior to the launch of the vaccine campaign revealed that 52.6% of HCWs indicated a willingness to receive a vaccine as soon as possible, while 35.6% reported preferring to wait for a few months before receiving one, and 11.8% indicated that they would never agree to receive any potential vaccine [ 23 ]. A systematic review regarding the acceptability of the COVID-19 vaccine found that the proportion of HCWs that intent to accept the COVID-19 vaccination was 55.9% [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study of HCWs in Saudi Arabia showed that the intention of men to be vaccinated is nearly 1.5 times higher than that of women. 27 This may be because females were more concerned about vaccines and diseases than males and thus were more concerned about the safety and effectiveness of vaccines. 28 HCWs were more willing to receive a COVID-19 vaccine as their age increased.…”
Section: Discussionmentioning
confidence: 99%
“… 33 A study by Barry et al reported that HCWs were 60% less willing to accept COVID-19 vaccines if they were hastily administered without evidence-based testing. 27 A recent study from the United States provided a detailed explanation of COVID-19 vaccine development, which drew attention from the medical community and may reduce doubts about COVID-19 vaccines among HCWs. 34 As CBS News reported We have a lot more work to do to get HCWs to take the vaccine.…”
Section: Discussionmentioning
confidence: 99%